Research Factors Affecting the Working Motivation of Employees at Accommodation Facilities in Danang - Trinh Le Tan; Phan Vu Tram Anh; Pham Nguyen Phuong Nhu; Tran Thi Anh Thu; Vien Dinh Anh Tuan; Hoang Ngoc Hung (Training & Research Institute - Jeramba Ilmu Sukses, 2021)
Work motivation is one of the burning issues for businesses and society, bringing great influence to individuals and organizations, so the team has studied the influencing factors and made recommendations to improve the quality of work. Recognizing issues affecting work motivation of employees at accommodation establishments in Da Nang. The author does this research to find out the factors that affect work motivation and from that offers the solution. The objective of the study is to find out the motivational factors that affect employees at accommodation establishments, thereby making reasonable suggestions to improve motivation. This study is carried out using quantitative methods and hypotheses, models of domestic and foreign studies. The surveyed employees are those who have been working in accommodation business establishments. The data analysis methods used in this paper are Cronbach and EFA methods, correlation, and regression. The results show that there are 5 factors affecting motivation including (1) Self-recognition; (2) Company Relationship; (3) Working Environment; (4) Job Characteristics; (5) Salary & Bonus. In which Self-recognition is considered the most important factor. Research-based on real problems, help businesses staying in Da Nang to see the problem and improve benefits, training policies for employees to increase work performance better to increase revenue, reduce employee turnover rate... and other issues.